Simulation of Sustainability and Energy Efficiency of NH3/CH4 Co-firing Flames in Swirl Combustors - Mondal, Mithun; Manshoor, Bukhari; Zaman, Izzuddin; Didane, Djamal Hissein; Abdul Haq, Reazul Haq; Abdul Ghafir, Mohammad Fahmi; Kamaruddin, Kamarul-Azhar; Baharuddin, Nurhayati; Ghazali, Mohd Fairusham; Kumar, Sudher (International Journal of Integrated Engineering, 2025)
Ammonia has emerged as a promising candidate due to its carbon-free and renewable nature. As a green energy carrier, ammonia can significantly reduce greenhouse gas emissions, but its utilization as a fuel faces challenges, including lower laminar flame speed, lower adiabatic flame temperature, higher ignition energy, narrower flammability limits, and increased nitrogen oxide emissions. To investigate their sustainability and energy efficiency, the study aims to simulate NH3/CH4 co-firing flames in a swirl combustor. The research focuses on premixed NH3/CH4/air reactants with varying methane fractions (0%, 25%, 50%, 75%, and 100%) at standard atmospheric pressure. The study simulates the steady flow field using ANSYS Fluent and the RNG k-? model and uses the results for unsteady simulations. Through the simulation, it indicates a trade-off between CO2 and NOx emissions. High CO2 emissions correspond to the complete combustion of methane, while low CO2 emissions indicate incomplete combustion, resulting in unburned methane. From the simulation results, 25% of methane fraction, with its highest energy efficiency and temperature, emerges as the most sustainable despite producing unwanted NOx emissions. Overall, 25% of methane fraction results are identified as the optimal mixture for energy production, highlighting the need for balancing efficiency and emission controls in sustainable combustion processes.